From food subsidies to cash transfers: Assessing economy-wide benefits and trade-offs in Egypt - Breisinger, Clemens; Kassim, Yumna; Kurdi, Sikandra; Randriamamonjy, Josee; Thurlow, James (Oxford University Press, 2024)
Food is a vital part of poor households' budgets and so subsidizing staple foods would appear to be an obvious pro-poor policy. Indeed, most countries in North Africa have prioritized large national subsidy programs for staple foods and fuels as their main social safety net. However, these programs account for significant shares of government spending and often drive fiscal deficits, especially when import prices rise. In this paper we use a dynamic Computable General Equilibrium model to evaluate the trade-offs between reducing poverty and managing fiscal balances. The modeling framework allows us to measure the efficiency costs of subsidies compared to cash transfers - switching to the latter is an emerging regional trend. We analyze these issues through a detailed case study of Egypt, where efforts to replace food subsidies with cash transfers is already underway. Data is also available in Egypt to design scenarios that realistically reflect potential targeting effectiveness and administrative costs. We show that replacing broad food subsidies with targeted cash transfers of roughly equivalent fiscal costs can improve the welfare of the poorest households, but the continuation of fiscal deficits results in a deceleration of economic growth. The latter gradually reduces welfare gains for the poor and leads to substantial welfare losses for middle-income households who lose access to subsidies without benefitting from cash transfers. Our findings highlight the political challenges facing subsidy reform programs.